Distinction between Mitochondrial Antibody-Positive and -Negative Primary Biliary Cholangitis - Venkata Vinod Kumar Matli; David F Dies; Sudha Pandit; Gregory Wellman; James D. Morris (Case Reports in Gastroenterology, 2023)
Antimitochondrial antibody-positive primary biliary cholangitis (AMA-pos PBC) is an autoimmune disorder in which monoclonal antibodies are produced against epitopes in the mitochondrial membranes of biliary epithelial cells, resulting in progressive nonsuppurative biliary cholangitis. Up to 5% of patients lack these autoantibodies, termed antimitochondrial antibody-negative (AMA-neg) PBC. Although a somewhat new variant of AMA-pos PBC, it is not an overlapping syndrome. Few studies to date have described this phenomenon. An 87-year-old woman was referred to our clinic with elevated serum alkaline phosphatase (714 U/L). She reported fatigue but no other symptoms. A physical examination revealed a benign lesion and bilateral lower extremity swelling secondary to lymphedema. The serological profile was significant for a high antinuclear antibody titer (>1:2,560) with a centromere pattern and negative for antimitochondrial antibody (AMA). The hepatitis panel was negative for viruses A, B, and C. Her serum immunoglobulin G level was 871 mg/dL (normal, <1,600 mg/dL). The rest of the serological tests, including anti-smooth muscle antibodies (ASMA) and anti-liver/kidney microsomal antibodies, were negative. Computed tomography of the abdomen and pelvis without contrast showed normal liver parenchyma and no acute intra-abdominal pathology. Histopathology indicated florid duct lesions. The background parenchyma showed no significant steatosis, and inflammatory changes were limited to the portal areas. Periodic acid-Schiff staining revealed intact hepatic parenchyma and architecture. The patient was diagnosed with AMA-neg PBC and responded well to ursodeoxycholic acid therapy. This case highlights the importance of recognizing AMA-neg PBC as a variant of AMA-pos PBC and differentiating between them. Autoimmune cholangitis is a vague and imprecise condition. All patients with AMA-negative PBC should be tested for other PBC-specific autoantibodies. Although the prognosis and bile duct damage and loss are worse in AMA-neg PBC for unknown reasons, treatment remains the same for both.